Comparative Efficacy and Safety of Ustekinumab and Secukinumab in the Treatment of Generalized Pustular Psoriasis: A 48-Week Retrospective Cohort Study with Genetic Background Analysis - Ruan SF; Su X; Xiao Z; Zhang Y; Lin T; Luo R; Xiang N; Cheng B; Gong T; Ji C (Dove Medical Press, 2024)
Shi-Fan Ruan,1- 3,* Xinhong Su,1,2,* Zhixun Xiao,1,2,* Yihua Zhang,1,2,* Tingting Lin,1,2 Renwei Luo,1,2 Niu Xiang,1,2 Bo Cheng,1- 3 Ting Gong,4 Chao Ji1- 3 1Department of Dermatology, The First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People's Republic of China; 2Key Laboratory of Skin Cancer of Fujian Higher Education Institutions, Fuzhou, Fujian, 350000, People's Republic of China; 3Fujian Provincial Clinical Research Center for Immune Skin Diseases, Fuzhou, Fujian, 350000, People's Republic of China; 4Central Laboratory, The First Affiliated Hospital of Fujian Medical University, Fuzhou, Fujian, 350000, People's Republic of China*These authors contributed equally to this workCorrespondence: Ting Gong, Central Laboratory, The First Affiliated Hospital of Fujian Medical University, 20 Chazhong Road, Fuzhou, Fujian, 350000, People's Republic of China, Email gongtingfy@fjmu.edu.cn Chao Ji, Department of Dermatology, The First Affiliated Hospital of Fujian Medical University, 20 Chazhong Road, Fuzhou, Fujian, 350000, People's Republic of China, Email jichaofy@fjmu.edu.cnPurpose: Recent studies have shown that novel biologics may provide significant clinical benefits for patients with generalized pustular psoriasis (GPP). Ustekinumab and secukinumab have been approved in Japan for GPP treatment in adult patients. However, the differences in efficacy and safety of these two drugs in GPP are not known.Aim: Based on the genetic background, we aimed to compare the efficacy and safety of secukinumab and ustekinumab in patients with GPP.Methods: Patients with moderate to severe GPP who were treated with ustekinumab/secukinumab at our department from July 2019 to May 2022 were included in this study and followed up for 48 weeks. The difference in efficacy between ustekinumab and secukinumab was evaluated by assessing changes in body temperature, laboratory indices, recovery of skin lesions, and changes in quality of life. Additionally, we collected patients' saliva for genotyping and explored the effect of CARD14 genetic mutations on clinical efficacy.Results: A total of 65 patients (32 adults and 33 children) with moderate to severe GPP were included in this study. 31 patients received ustekinumab therapy, and 34 patients were treated with secukinumab. Secukinumab demonstrated superiority to ustekinumab, as evidenced by a higher GPPASI 90 response at week 2. Additionally, the efficacy of ustekinumab and secukinumab was found to be independent of the presence of the CARD14 mutation.Conclusion: Secukinumab is superior to ustekinumab in rapidly clearing the skin and improving health-related quality of life. Moreover, the responses to ustekinumab/secukinumab in patients were not influenced by CARD14 gene mutations.Keywords: generalized pustular psoriasis, secukinumab, ustekinumab, clinical efficacy, safety, gene mutations